STUDI KEPUSTAKAAN ASUPAN NATRIUM DAN KALIUM DENGAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Putu Arminiati; Ni Komang Wiardani; Gusti Ayu Kusumayanti (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
Hypertension or high blood pressure often as the silent killer. Hypertension which condition blood pressure ≥ 140 mmHg (systolic pressure) and/ or ≥ 90 mmHg (diastolic pressure). Many factors play a role in hypertension, one of them were sodium and potassium intake.This study aims to analyze the relation between sodium and potassium intake with blood pressure. This research is a literature study in May 2020. Subjects in this study male and female hypertension patients ≥ 30 years old. Data researches such as sodium, potassium intake and blood pressure were obtained from researched articles, tabulated and analyzed. Data were qualitative analyzed. The results of this research more hypertension patients female, in age range between ≥ 30 years old - ≥ 80 years old. The range sodium intake between 394,75 – 2432,1, The range of percentages 60,3 - 82.4% and The range potassium intake between 1012,72 - 2287,24, The range of percentages 50 – 89,8 %. Based on the results, it was recognized that 4 journals stated the relationship between sodium intake with the incidence of hypertension and 4 journals stated there was no relationship between sodium intakes with the incidence of hypertension, whereas all journals stated there was no relationship between potassium intakes with hypertensionKeywords: blood pressure, sodium and potassium intake.